THE INFLUENCE OF CETIRIZINE ON THE CONCENTRATION OF sCD14 IN BLOOD OF THE CHILDREN WITH ATOPIC DERMATITIS - E.S. Nisheva; I.A. Zvyagina; L.G. Valetova; N.B. Platonova; T.G. Butyrina; A.V. Avvakumova; N.N. Kaplin ("Paediatrician" Publishers LLC, 2006)
66 children with atopic dermatitis aged 1B2 years and 21 children as A control group were examined in an effort to study the impact of cetirizine on the concentration of scd14 in case of allergic disbeases in children. 33 children with atopic dermatitis had referbences in anamnesis on obstructive bronchitis. Children with atopic dermatitis were divided into 3 approximately equal groups - the first group took cetirizine during 2 weeks, the second group - during 4 months, for the third group cetirizine was not given. The level of sCD14 was determined in children's blood by immuneb enzyme analysis method before treatment, directly after treatment with cetirizine and in 2 months after it. In children with allergic diseases the level of sCD14 was 50% lower than in children with out allergy. The short course of cetirizine treatment transiently reduced clinical presentations of atopic dermatitis, but didn't have effect on sCD14 content. Prolonged therapy with cetirizine not only improved the condition of children with atopic dermatitis and decrease the occurrence of obstructive bronchitis in these cases, but also resulted in considerable increase in the concentration of sCD 14 in blood of these patients. We presume the therapeutic and prophylactic effects of cetirizine in allergic diseases in many respects are conditioned by its capacity to improve functions of macrophages in response to infectious and allergic stimuli.Key words: sCD 14, atopic dermatitis, cetirizine, children, treatment.